Inflammatory markers are associated with quality of life, physical activity, and gait speed but not sarcopenia in aged men (40–79 years). Issue 6 (15th September 2021) - Dupont, Jolan; Antonio, Leen; Dedeyne, Lenore; O'Neill, Terence W.; Vanderschueren, Dirk; Rastrelli, Giulia; Maggi, Mario; Bártfai, György; Casanueva, Felipe F.; Giwercman, Aleksander; Słowikowska‐Hilczer, Jolanta; Punab, Margus; et al.
Abstract: Background: Age‐related chronic low‐grade inflammation (inflammaging) is one of the proposed mechanisms behind sarcopenia. However, findings regarding inflammatory markers in sarcopenic older adults are conflicting. This study aimed to determine the association between inflammatory markers, prevalent as well as incident sarcopenia, sarcopenia‐defining parameters, quality of life (QoL), and physical activity in middle‐aged and older men. Methods: Men aged 40–79 years (mean 59.66 ± 11.00y) were recruited from population registers in eight European centres for participation in the European Male Aging study (EMAS). Subjects were assessed at baseline (2003–2005) and again after a median follow‐up of 4.29 years. In 2577 participants, associations between baseline inflammatory markers [high‐sensitive C‐reactive protein (hs‐CRP), white blood cell count (WBC), albumin] and baseline physical activity (PASE) and QoL (SF‐36) were analysed. In the Leuven and Manchester cohort ( n = 447), data were available on muscle mass (whole‐body dual X‐ray absorptiometry) and strength. In this subgroup, cross‐sectional associations between baseline inflammatory markers and sarcopenia‐defining parameters (handgrip strength, chair stand test, appendicular lean mass, and gait speed) and prevalent sarcopenia were examined. In a further subgroup ( n = 277), associations with knee extensor strength were explored. Longitudinally, predictive value of baseline inflammation on functional decline, physical activity, QoL, and incident sarcopenia was examined. Subgroup analyses were performed in subgroups with chronic inflammation and stratified by age. Linear and logistic regressions were used, adjusted for age, body mass index, centre, and smoking. Results: At baseline, hs‐CRP and WBC were negatively associated with PASE score (hs‐CRP: β = −7.920, P < 0.001; and WBC: β = −4.552, P < 0.001) and the physical component score of SF‐36 (hs‐CRP: β = −1.025, P < 0.001; and WBC: β = −0.364, P < 0.001). Baseline WBC levels were negatively associated with gait speed (β = −0.013; P = 0.025), quadriceps isometric 90° (β = −5.983; P = 0.035) and isokinetic 60°/s peak torque/body weight (β = −5.532; P = 0.027). The prevalence of sarcopenia at baseline was 18.1% ( n = 81). Of those without sarcopenia at baseline, 64 (18.6%) satisfied criteria for sarcopenia at follow‐up. There were no significant associations between baseline inflammatory markers and either prevalent or incident sarcopenia, or change in level of sarcopenia‐defining parameters between baseline and follow‐up. Conclusions: In middle‐aged and older men, hs‐CRP and WBC were negatively associated with QoL and PASE scores, while WBC was negatively associated with gait speed and knee strength. Associations with hs‐CRP remained significant in all ages, whereas WBC levels were only associated with PASE, gait speed and knee strength in older adults (60–79 years). Baseline inflammatory markers (hs‐CRP, WBC and albumin) did not predict functional decline, decline in physical activity, decreased QoL or incident sarcopenia.